UV Cured Boronic Acid Based Fluorescence Sensor for the Determination of Glucose - (:unkn) unknown (AIDIC SERVIZI SRL, 2013)
The use of polymers is finding a significant place in development of sensors. Better selectivity and rapid measurements have been achieved by replacing classical sensor materials with functions of polymers. Several receptors have been employed to detect glucose in fluorescence sensors, and these include enzymes such as glucose oxidase, glucose dehydrogenase and hexokinase/glucokinase, bacterial glucose-binding protein, and boronic acid derivatives. Boronic acid has a important role in the design of glucose sensors. The sensing membrane was prepared with p-Vinylphenylboronicacid (VPBA), Hydroxyethylmethacrylate (HEMA) and Poly(ethylene glycol) diacrylate (PEG-DA). The membran is capable of determining glucose between 0.1 ppm and 0.7 ppm. It can be completely regenerated by using distilled water. The sensor performance characteristics such as response time, dynamic working range and sensitivity were reported. The optical sensor was stable, cost effective, easy to prepare, rapid and simple for the determination of glucose. The results suggest that the sensor can be used as glucose sensors to determine glucose.
Keywords: IMMOBILIZATION; SACCHARIDES